Analisis Kemampuan Literasi Numerasi pada Materi Pecahan Berbasis Masalah Kehidupan Nyata Siswa Sekolah Dasar - Abdul Majid (Tarunateach: Journal of Elementary School, 2026)
This study aims to analyze elementary school students’ mathematical numeracy literacy skills based on real-life contexts. Numeracy literacy is a fundamental competence that enables students to understand, use, and interpret mathematical concepts in daily situations. This research employed a quantitative descriptive approach. The study was conducted at Madrasah Aliyah Swasta darud Dakwah Wal Irsyad Baru Baru Tanga, Pangkajene and Islands Regency, during August–September 2025. The research subjects were elementary school students selected purposively. Data were collected using a numeracy literacy test designed with daily life contexts, covering number operations, measurement, data interpretation, and simple problem-solving. Data analysis was carried out using descriptive statistics, including mean scores and percentage achievement levels. The results revealed that students’ numeracy literacy skills were generally in the moderate category. Students showed adequate ability in performing basic calculations; however, difficulties were found in understanding contextual problems, selecting appropriate strategies, and interpreting mathematical results within real-life situations. These findings indicate that mathematics learning at the elementary level still tends to emphasize procedural skills rather than contextual understanding. Therefore, strengthening contextual-based mathematics instruction is essential to improve students’ numeracy literacy skills and their ability to apply mathematics meaningfully in everyday life.